Crestal Bone Changes in Different Implants Designs: A Prospective Clinical Trial - Caetano, Gustavo M.; Pauletto, Patrícia; Mezzomo, Luis A.; Rivaldo, Elken G. (European Journal of Dentistry, 2019)
Objective Several modifications, such as changes in the implant–abutment connection, have been suggested in studies on dental implants to better preserve the peri-implant bone level. The aim of this study was to prospectively compare crestal bone level changes between two different implant designs—tissue level (TL) and bone level (BL).Materials and Methods The sample comprised 18 patients, on whom a total of 30 hydrophilic tissue- and bone level implants were placed (SLActive, Straumann Institut AG, Basel, Switzerland), in the posterior region of the maxilla or the mandible. Impressions were taken after 45 days of healing. Then, cemented-retained metalloceramic crowns were fabricated and installed. Marginal bone level changes were assessed by the paralleling technique of periapical radiographies, on both mesial and distal aspects of each implant, at the moment of the implant placement and after 1 year of loading. Photoshop software was used to perform linear measurements by a single and calibrated examiner.Statistical Analysis The Mann–Whitney test at a 5% significance level was used to compare the bone changes among the implants assessed.Results A significantly lower (p = 0.048) bone remodeling was observed on bone level implants (0.05 mm), when compared to tissue level implants (0.47 mm; p = 0.048). The average marginal bone level changes at the distal aspect did not show any statistically significant difference (p = 0.325).Conclusions Tissue level implants presented greater bone loss in the mesial surface than bone level implants. Both designs presented stable and clinically acceptable bone crests.
Keywords: bone level; dental implant; marginal bone; tissue level